Examining Dividend-Related Abnormal Returns and Trading Volume in IDX Manufacturing 2016-2020: Analisis Kenaikan Abnormal dan Aktivitas Volume Perdagangan Sebelum dan Sesudah Tanggal Ex-Dividend pada Sektor Manufaktur yang Terdaftar di IDX Periode 2016-2020 - Dyah Agung; Heri Widodo (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to analyze the market reaction to ex-date dividends within a specific research period. The research period consists of 5 days before the dividend ex-date, 1 day for estimation, and 5 days after the dividend ex-date. A descriptive method was employed for sample selection, focusing on 6 companies in the manufacturing sector over 5 periods from 2016 to 2020. Secondary data was utilized for analysis. The paired sample test for abnormal returns, suitable for normally distributed data, was used to assess the impact of ex-date dividends. Additionally, the Wilcoxon signed rank test was applied to trading volume activity due to its non-uniform distribution. The results indicate a significant difference between trading volume activity before and after the ex-date dividend. The implications of these findings provide insights into the market reaction to ex-date dividends in the manufacturing sector, contributing to a better understanding of dividend-related phenomena in financial markets. Highlights: Market reaction to ex-date dividends in the manufacturing sector. Analysis of abnormal returns and trading volume activity. Significant difference before and after ex-date dividends. Keywords: Ex-date dividends, market reaction, manufacturing sector, abnormal returns, trading volume activity.